Pengaruh Green Marketing terhadap Purchase Intention Melalui Brand Image Sebagai Variabel Intervening - Permana, Madani Prima; Saputri, Marheni Eka (Ekonomis: Journal of Economics and Business, 2024)
This study aims to determine the effect of Green Marketing on purchase intention of Ikea products through brand image as an intervening variable. This study used a quantitative method with the analytical technique used, namely Partial Least Square-Structural Equation Model (PLS-SEM) analysis. The sampling technique used is the non-probability sampling technique, with a total of 400 respondents participating. The results of this study are that green marketing has a positive and significant effect on purchase intention, green marketing has a positive and significant effect on brand image, brand image has a positive and significant effect on purchase intention, and green marketing has a positive and significant effect on purchase intention through brand image as an intervening variable on Ikea products.